1990
DOI: 10.1073/pnas.87.19.7360
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of a calmodulin-related gene during transformation of human mammary epithelial cells.

Abstract: A human cDNA library obtained from cultured normal mammary epithelial cells (HMECs) was searched by subtractive hybridization for genes whose decrease in expression might be relevant to epithelial transformation. One clone identified by this procedure corresponded to a 1.4-kilobase mRNA, designated NB-1, whose expression was decreased >50-fold in HMECs tumorigenically transformed in vitro after exposure to benzo[alpyrene and Kirsten sarcoma virus. Sequence analysis of NB-1 cDNA revealed an open reading frame w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 28 publications
(25 reference statements)
2
43
0
Order By: Relevance
“…In normal breast epithelial cultures, the gene was detectable in 13/17 instances, but not found in either tumour-derived epithelial cultures or in tumour cell lines derived from breast or bone. This concurs with other studies that have shown its expression in cultured normal, but not malignant, mammary epithelial cells (Yaswen et al, 1990;Stampfer and Yaswen, 1993). It has also been suggested that in normal breast, the gene is down-regulated in vitro (Yaswen et al, 1990), which may explain the lack of expression of NB-1 in four normal epithelial cultures.…”
Section: Genetic Analysissupporting
confidence: 91%
See 4 more Smart Citations
“…In normal breast epithelial cultures, the gene was detectable in 13/17 instances, but not found in either tumour-derived epithelial cultures or in tumour cell lines derived from breast or bone. This concurs with other studies that have shown its expression in cultured normal, but not malignant, mammary epithelial cells (Yaswen et al, 1990;Stampfer and Yaswen, 1993). It has also been suggested that in normal breast, the gene is down-regulated in vitro (Yaswen et al, 1990), which may explain the lack of expression of NB-1 in four normal epithelial cultures.…”
Section: Genetic Analysissupporting
confidence: 91%
“…This concurs with other studies that have shown its expression in cultured normal, but not malignant, mammary epithelial cells (Yaswen et al, 1990;Stampfer and Yaswen, 1993). It has also been suggested that in normal breast, the gene is down-regulated in vitro (Yaswen et al, 1990), which may explain the lack of expression of NB-1 in four normal epithelial cultures. The sensitivity of the PCR, in theory capable of amplifying message from a single cell, unequivocally demonstrates that our cultures contained tumour and not normal epithelial cells.…”
Section: Genetic Analysissupporting
confidence: 91%
See 3 more Smart Citations